PROSTATE-SPECIFIC ANTIGEN (PSA) RAPID DIAGNOSTIC TESTS COMPARED WITH SRY GENE FOR DETECTING MALE COMPONENT IN VAGINAL SWABS - Henky, -; Arijana, I G. K. N. (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
Proving intercourse signs on sexual assault victims still become a major challenge for forensic physicians in Indonesia.  Many cases unsolved due to minimal evidences. One of the difficulties is evincing ejaculation in vagina.  Most of forensic laboratories only depend on spermatozoa examination to find ejaculate.  Surely, it is difficult to find spermatozoa if the perpetrators are azoospermia.  Moreover, this examination may give false negative results as well as low sensitivity, especially in women who have washed their vagina. However, nowadays, there is a rapid test to detect PSA in seminal fluid which is very practical, quick, and inexpensive.  This study will show the performance of PSA rapid test to detect male component in vaginal swabs taken from sexually assaulted victims. A cross sectional study was conducted between October 2012 and December 2012.  Sixteen vaginal swabs had been collected consecutively from raped women who were examined in gynecologic emergency ward Sanglah Public Hospital.  The vaginal swabs were tested with PSA rapid test and extracted for SRY gene analysis as a gold standard to confirm male genetic material.  The result of this study shows that PSA rapid test diagnostic values to detect male component in vaginal swabs are sensitivity 84.62%, specificity 100%, PPV 100%, NPV 60%, LR (+) 100%, LR (-) ~, and accuracy 87.5%.  These values are better than spermatozoa examination. Based on this study, PSA rapid test is highly recommended to take the place of spermatozoa examination as a new standard for proving sexual intercourse in Indonesia.
Keywords: PSA, SRY, Sexual Assault